Geometric modeling of the processes of excavation by an excavator in order to prevent damage to the pipeline wall - F. N. Pritykin; I. S. Kuznetsov (Омский научный вестник)
When controlling the motion of the excavator bucket, the operator controls the translational motions in the hydraulic cylinders, which are generally independent. However, ensuring the motion of the cutting edge of the bucket along a given trajectory (for example, along a horizontal straight line) requires certain skills and additional concentration of attention from the operator. This significantly affects the fatigue of the operator during these works. In this case, it becomes relevant to solve the problem of developing an automated control system that makes it possible to calculate the change in the angles of rotation in the rotary joints of the excavator, which provide the specified motion of the bucket. In this case, the operator can only indicate the start and target points of the trajectory and the direction of motion of the bucket. In the article, based on the research, an algorithm has been developed that allows you to simulate the motion of points of an excavator bucket with a given distance from the upper edge of the pipeline. The results of computer simulation of the motion of the excavator manipulator are presented.